Chlorine-induced high temperature corrosion of HVAF-sprayed Ni-based alumina and chromia forming coatings - Sadeghimeresht, Esmaeil; Reddy, Liam; Hussain, Tanvir; Markocsan, Nicolaie; Joshi, Shrikant (Elsevier, 2018)
Chlorine-induced corrosion of HVAF-sprayed Ni21Cr and Ni5Al coatings was investigated in 5 vol.% O2 + 500vppm HCl + N2 with and without KCl at 600 °C up to 168 h. Both coatings were protective in the absence of KCl. With KCl, Ni21Cr degraded through a two-stage mechanism: 1) formation of K2CrO4 followed by diffusion of Cl− through the oxide grain boundaries to yield chlorine and a non-protective oxide, and 2) inward diffusion of chlorine though defects in the non-protective oxide, leading to breakaway oxidation. Cl−/Cl2 could not diffuse through the protective alumina scale formed on Ni5Al, hence the corrosion resistance increased.